Open data and model integration through generic model agent toolkit in CyberWater framework. (June 2022) - Chen, Ranran; Luna, Daniel; Cao, Yuan; Liang, Yao; Liang, Xu
Abstract: The CyberWater project is created to develop an open data and open model integration framework for studying complex environmental and water problems, where diverse online data sources can be directly accessed by diverse models without any need of users' extra effort on the tedious tasks of data preparation for their models. We present our design and development of a novel generic model agent toolkit in the context of CyberWater, which enables users to integrate their models into the CyberWater system without writing any new code, significantly simplifying the data and model integration task. CyberWater adopts a visual scientific workflow system, VisTrails, which also supports provenance and reproducible computing. Our approach and the developed generic model agent toolkit are demonstrated, via CyberWater framework, with automated and flexible workflows through integrating data and models using real-world use cases. Two popular hydrological models, VIC and DHSVM, are used for illustrations. Highlights: A novel approach of model integration is presented. A generic model agent toolkit for our approach is developed for users' data and model integration. The toolkit enables a user to construct a model agent for model integration without coding. The toolkit is generic and facilitates the construction of model agents for diverse models. The toolkit is demonstrated via CyberWater framework with real world use cases.